PH and temperature stability of (−)-epigallocatechin-3-gallate-β-cyclodextrin inclusion complex-loaded chitosan nanoparticles. (20th September 2016) - Liu, Fei; Majeed, Hamid; Antoniou, John; Li, Yue; Ma, Yun; Yokoyama, Wallace; Ma, Jianguo; Zhong, Fang
Graphical abstract: Possible changes of EGCG-loaded CSNs and EGCG-ICs after altering the pH value or temperature of nanoparticle suspensions. Highlights: Oxidative stability of EGCG incorporated into ICs and CSNs were both investigated. EGCG-ICs and related CSNs were physically unstable at higher pH and temperature. Antioxidant activities of CSNs decreased more compared to EGCG-ICs and free EGCG. Extreme entrapment of EGCG in aggregated CSNs inhibited the antioxidant activities. Nanostructure of CSNs was lost but the activity of encapsulated EGCG may remain. Abstract: The oxidative stability of (−)-epigallocatechin-3-gallate (EGCG) incorporated as inclusion complexes (ICs) in sulfobutylether-β-cyclodextrin sodium (SBE-β-CD) and then ionotropically crosslinked with chitosan hydrochloride (CSH) into nanoparticles were investigated. EGCG-loaded CSH-SBE-β-CD nanoparticles (CSNs) were physically unstable at higher pH and temperature. The particle size of CSNs was unchanged in the pH range of 3–5, but the microenvironment of EGCG-IC appeared to be intact until the pH increased to 6.5 by fluorescence spectroscopy. The physical structure of EGCG-ICs was also affected during storage in addition to CSNs, which was further affected as temperature increased from 25 to 55 °C. The decrease in antioxidant activities of EGCG-ICs and free EGCG with increasing pH, storage time and temperature were modest compared to the prominent decreases in antioxidant activities of EGCG-loaded CSNs. The extreme entrapment of EGCG-ICs and/or free EGCG in the aggregated CSNs restricted the release of EGCG, thus inhibiting the antioxidant activities.